Transposase expression, element abundance, element size, and DNA repair determine the mobility and heritability of PIF/Pong/Harbinger transposable elements - Redd, Priscilla S.; Payero, Lisette; Gilbert, David M.; Page, Clinton A.; King, Reese; McAssey, Edward V.; Bodie, Dalton; Diaz, Stephanie; Hancock, C. Nathan (Frontiers in Cell and Developmental Biology, 2023)
Class II DNA transposable elements account for significant portions of eukaryotic genomes and contribute to genome evolution through their mobilization. To escape inactivating mutations and persist in the host genome over evolutionary time, these elements must be mobilized enough to result in additional copies. These elements utilize a “cut and paste” transposition mechanism that does not intrinsically include replication. However, elements such as the rice derived mPing element have been observed to increase in copy number over time. We tested several parameters that affect the excision and insertion of mPing and its related elements in yeast. Unlike other element superfamilies, increased transposase protein expression increases mobilization frequency of these elements. Smaller element size increased both the frequency of excision and insertion of these elements. The effect of yeast ploidy on element excision, insertion, and copy number provided evidence that homology dependent repair allows for replicative transposition. These elements were found to preferentially insert into yeast rDNA repeat sequences. These insights in the behavior of these elements provide important clues into how class II transposable elements have shaped eukaryotic genomes.